The Aventine Circle in 4th-century Rome - da Silva Martins, Maria Cristina (Romanitas - Revista de Estudos Grecolatinos, 2021)
This paper aims to spread The Aventine Circle, a kind of school of Christian asceticism, biblical and language studies, founded by Marcela (later Saint Marcella), in fourth century Rome, attended by other ladies of the Roman aristocracy, also later sanctified. In the meetings of this circle, St. Jerome acted as a teacher and spiritual advisor. A brief historical contextualization of Christianity from the IV century, as well as the ideology conveyed by the Church Fathers about women, is also part of this article.